2017
DOI: 10.1038/s41699-017-0019-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence of exciton capture by mid-gap defects in CVD grown monolayer MoSe2

Abstract: In two dimensional (2D) transition metal dichalcogenides, defect-related processes can significantly affect carrier dynamics and transport properties. Using femtosecond degenerate pump-probe spectroscopy, exciton capture, and release by mid-gap defects have been observed in chemical vapor deposition (CVD) grown monolayer MoSe 2 . The observed defect state filling shows a clear saturation at high exciton densities, from which the defect density is estimated to be around 0.5 × 10 12 /cm 2 . The exciton capture t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 53 publications
7
72
0
Order By: Relevance
“…To further understand the dynamics of free carriers and excitons, the peak values ΔσRe and ΔσIm as a function of pump fluence are studied in Figure b. The peak value ΔσRe shows a trend of saturation with the pump fluence, which suggests nonlinear absorption by the free carriers and more excitons would be formed at high pump fluence . Based on previous theoretical model, the response of nonlinear free carrier absorption could be attributed to the strong electron–photon interaction and electron–impurity interaction .…”
Section: Resultsmentioning
confidence: 99%
“…To further understand the dynamics of free carriers and excitons, the peak values ΔσRe and ΔσIm as a function of pump fluence are studied in Figure b. The peak value ΔσRe shows a trend of saturation with the pump fluence, which suggests nonlinear absorption by the free carriers and more excitons would be formed at high pump fluence . Based on previous theoretical model, the response of nonlinear free carrier absorption could be attributed to the strong electron–photon interaction and electron–impurity interaction .…”
Section: Resultsmentioning
confidence: 99%
“…With resonant detection, the reflection change is dominated by the absorption coefficient change due to the phasespace filling effect. 8,9 For both samples (exfoliated MoSe 2 on the Si substrate and the MoSe 2 thin film grown on the sapphire substrate by MBE), the reflection change is proportional to the absorption coefficient change, according to the calculation with the transfer matrix method (supplementary material). 8,9 Thus, the response of negative reflection change ∆R means that the absorption coefficient decreases after the pump excitation, which is consistent with the Pauli blocking/repulsion induced by the phase-space filling effect.…”
Section: -2mentioning
confidence: 99%
“…6 While oxygen impurities occupying chalcogen vacancy sites can eliminate the mid-gap states, 7 oxygen impurities taking up molybdenum vacancy sites keep those mid-gap states and play the role as effective carrier trappers. 8,9 Comparing with exfoliated and CVD synthesized samples, studies on the photoexcited carrier dynamics in MBE-grown TMDs are rare. Our previous work has shown that one of the main a Author to whom correspondence should be addressed: yaguo.wang@austin.utexas.edu 2166-532X/2018/6(5)/056103/7 6, 056103-1 © Author(s) 2018…”
mentioning
confidence: 99%
“…the transition from the localized defect states which possess broad momenta to high energy states in the conduction band, becomes available, leading to an increase in the absorption. In our previous study 16 , oxygen impurities have been proposed to be responsible for the carrier-trapping events, because the defect trapping effect could only be observed in CVD grown films but not in exfoliated flakes, and the oxygen content is only found in CVD as-grown films. Here, the fact that the defect-capturing-carrier signature can again be observed after the generation of oxygen impurities in the exfoliated sample by plasma irradiation, serves as strong evidence that oxygen impurities in MoSe2 samples are indeed the effective carrier-trapping defects.…”
mentioning
confidence: 99%